IMPLEMENTASI DATA MINING MENGGUNAKAN METODE DESKRIPSI UNTUK MENGETAHUI POLA PENENTUAN PENERIMA BANTUAN SISWA MISKIN (BSM) DI SMP N 3 DOLOKSANGGUL - Rusli Purba; Nelly Astuti Hasibuan; Edizal Hatmi (STMIK Budi Darma, 2019)
Poor Student Assistance is very helpful for students to meet the needs in learning activities and in completing the students themselves is very supportive in government programs that have to study nine years (preferably up to the upper secondary level), to help smooth the Poor Student Assistance which is directly to students and this does not aim for students who excel because it considers the condition of students. To find out the pattern of determining poor students' assistance recipients can be done by utilizing student data and poor student aid recipient data. Searching for patterns of determining students who receive aid from poor students is expected to be able to analyze the factors that greatly affect the recipients of poor student assistance. The method in accordance with the above problems using the Description Method, Description is one of the uses of data mining to explore and collect a lot of data. The description method is useful for characterizing or describing a condition, history, object.Keywords: Data Mining, Poor Student Assistance, Method Description